Chloroprene-based latex composition, method for producing chloroprene-based latex composition and aqueous adhesive
The chloroprene latex composition, with a specific chloroprene copolymer and polyvinyl alcohol ratio, addresses the stability and odor issues of existing compositions, resulting in enhanced storage, mechanical stability, and adhesive properties.
Patent Information
- Application Number
- JP2023172819
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-10-04
- Publication Date
- 2025-04-16
AI Technical Summary
Chloroprene latex compositions using polyvinyl alcohol as an emulsifier have lower storage stability and mechanical stability, and tend to form agglomerates under vibrations or mechanical shearing, while also having an odor.
A chloroprene latex composition containing a chloroprene copolymer and polyvinyl alcohol, where the chloroprene copolymer includes monomer units derived from chloroprene and a vinyl monomer with a carboxyl group, with specific mass ratios to enhance stability and reduce odor.
The composition achieves improved storage stability, mechanical stability, and reduced odor, while maintaining excellent adhesive properties such as initial peel strength, normal peel strength, water resistance, and heat resistance.
Smart Images

Figure 2025063533000001 
Figure 2025063533000002 
Figure 2025063533000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a chloroprene-based latex composition, a method for producing the chloroprene-based latex composition, and a water-based adhesive. [Background technology]
[0002] Chloroprene latex is used in a variety of fields, including as a water-based adhesive used in the production of civil engineering and construction, plywood, furniture, shoes, wetsuits, etc.; as a material for dip-molded products such as work gloves, laboratory gloves, and medical gloves, as well as rubber thread and balloons; and as a material for waterproof coating films in the civil engineering and construction fields.
[0003] Patent Document 1 discloses a polychloroprene latex composition obtained by emulsion polymerization of chloroprene and an ethylenically unsaturated carboxylic acid in the presence of a water-soluble polymer having a protective colloid effect. Patent Document 2 discloses a polychloroprene-based latex composition obtained by emulsion polymerization of chloroprene alone, or chloroprene and a monomer copolymerizable with chloroprene, in the presence of a polyoxyethylene alkyl ether having an HLB value of 14 to 19 and polyvinyl alcohol. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent No. 3294910 [Patent Document 2] JP 2005-008859 A Summary of the Invention [Problem to be solved by the invention]
[0005] Chloroprene-based latex compositions produced using polyvinyl alcohol as an emulsifier have excellent adhesion, and are therefore used, for example, as aqueous adhesives. However, chloroprene-based latex compositions produced using polyvinyl alcohol as an emulsifier tend to have lower storage stability and mechanical stability than chloroprene-based latexes using emulsifiers other than polyvinyl alcohol, and may produce aggregates, particularly when subjected to vibration during transportation or mechanical shear force from a stirrer or pump. In addition, chloroprene-based latex compositions may have an odor. It has been difficult to obtain a chloroprene-based latex composition with little odor and excellent storage stability and mechanical stability using conventional techniques.
[0006] The present invention has been made in view of the above circumstances, and provides a chloroprene-based latex composition which has little odor and is excellent in storage stability and mechanical stability, a method for producing the chloroprene-based latex composition, and an aqueous adhesive containing the chloroprene-based latex composition. [Means for solving the problem]
[0007] According to the present invention, there is provided a chloroprene-based latex composition comprising a chloroprene-based copolymer and polyvinyl alcohol, the chloroprene-based copolymer comprising monomer units derived from chloroprene and monomer units derived from a vinyl monomer containing a carboxyl group, the chloroprene-based copolymer comprising 0.70 to 5.00 parts by mass of monomer units derived from the vinyl monomer containing a carboxyl group per 100 parts by mass of the monomer units derived from chloroprene, and the chloroprene-based latex composition comprising 0.10 to 1.40 parts by mass of a vinyl monomer containing a free carboxyl group per 100 parts by mass of the monomer units derived from chloroprene.
[0008] Means for Solving the Problems The present inventors have conducted intensive studies and found that, in a chloroprene latex composition containing a chloroprene copolymer and polyvinyl alcohol, by highly adjusting the production conditions so that the chloroprene copolymer contains a specific amount of monomer units derived from a vinyl monomer containing a carboxyl group and the chloroprene latex composition contains a specific amount of a vinyl monomer containing a free carboxyl group, a chloroprene latex composition having little odor and excellent storage stability and mechanical stability can be obtained, leading to the completion of the present invention.
[0009] Various embodiments of the present invention will be described below. The embodiments described below can be combined with each other. [1] A chloroprene-based latex composition comprising a chloroprene-based copolymer and polyvinyl alcohol, the chloroprene-based copolymer comprising monomer units derived from chloroprene and monomer units derived from a vinyl monomer containing a carboxyl group, the chloroprene-based copolymer comprising 0.70 to 5.00 parts by mass of monomer units derived from the vinyl monomer containing a carboxyl group per 100 parts by mass of the monomer units derived from chloroprene, and the chloroprene-based latex composition comprising 0.10 to 1.40 parts by mass of a vinyl monomer containing a free carboxyl group per 100 parts by mass of the monomer units derived from chloroprene. [2] The chloroprene-based latex composition according to [1], wherein the chloroprene-based copolymer contains a graft copolymer containing a monomer unit derived from the chloroprene, a monomer unit derived from the vinyl monomer containing a carboxyl group, and a structure derived from polyvinyl alcohol. [3] The chloroprene latex composition according to [1] or [2], wherein the chloroprene copolymer contains 0.30 to 5.00 parts by mass of a structure derived from polyvinyl alcohol per 100 parts by mass of the chloroprene copolymer. [4] The chloroprene latex composition according to any one of [1] to [3], further comprising a nonionic surfactant. [5] The chloroprene-based latex composition according to any one of [1] to [4], wherein the vinyl monomer having a carboxyl group contains an α,β-unsaturated carboxylic acid. [6] A method for producing a chloroprene-based latex composition according to any one of [1] to [5], comprising a polymerization step of polymerizing raw material monomers including a chloroprene monomer and a vinyl monomer having a carboxyl group, in which polyvinyl alcohol and a surfactant are added in the polymerization step, and in which at least a part of the raw material monomers are added in portions after the initiation of polymerization while being cooled to below freezing point in the polymerization step. [7] An aqueous adhesive comprising the chloroprene-based latex composition according to any one of [1] to [5]. Effect of the Invention
[0010] According to the present invention, there are provided a chloroprene-based latex composition which has little odor and is excellent in storage stability and mechanical stability, a method for producing the chloroprene-based latex composition, and an aqueous adhesive containing the chloroprene-based latex composition. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The present invention will be described in detail below by illustrating the embodiments of the present invention. The present invention is not limited by these descriptions. The features of the embodiments of the present invention described below can be combined with each other. In addition, each feature can be an invention independently.
[0012] 1. Chloroprene-based latex composition The chloroprene latex composition according to the present invention contains a chloroprene copolymer and polyvinyl alcohol. The chloroprene copolymer according to the present invention contains a monomer unit derived from chloroprene and a monomer unit derived from a vinyl monomer containing a carboxyl group. The chloroprene copolymer according to the present invention contains 0.70 to 5.00 parts by mass of a monomer unit derived from a vinyl monomer containing a carboxyl group relative to 100 parts by mass of the monomer units derived from chloroprene. The chloroprene latex composition according to the present invention contains 0.10 to 1.40 parts by mass of a vinyl monomer containing a free carboxyl group relative to 100 parts by mass of the monomer units derived from chloroprene. According to the present invention, by adjusting the chloroprene copolymer to contain a specific amount of a monomer unit derived from a vinyl monomer containing a carboxyl group and the chloroprene latex composition to contain a specific amount of a vinyl monomer containing a free carboxyl group, a chloroprene latex composition having less odor and excellent storage stability and mechanical stability can be obtained. Furthermore, the aqueous adhesive containing the chloroprene-based latex composition has excellent adhesive properties such as initial peel strength, normal peel strength, water resistance, and heat-resistant adhesive strength, and has an appropriate softening point. Each component of the chloroprene-based latex composition will be described in detail below.
[0013] 1.1 Chloroprene copolymers In the present invention, the chloroprene copolymer means a polymer containing a monomer unit derived from 2-chloro-1,3-butadiene (hereinafter referred to as chloroprene). The chloroprene copolymer according to the present invention contains a monomer unit derived from chloroprene and a monomer unit derived from a vinyl monomer containing a carboxyl group. The chloroprene copolymer according to the present invention may also contain a structure derived from polyvinyl alcohol.
[0014] The vinyl monomer containing a carboxyl group may contain an α,β-unsaturated carboxylic acid. Examples of the α,β-unsaturated carboxylic acid include unsaturated monocarboxylic acids such as acrylic acid, methacrylic acid, crotonic acid, and 3-butenoic acid; unsaturated dicarboxylic acids such as maleic acid, fumaric acid, and itaconic acid; monoesters of unsaturated dicarboxylic acids such as monomethyl maleate, monomethyl fumarate, and monomethyl itaconate; unsaturated polycarboxylic acids; and esters of unsaturated polycarboxylic acids. The α,β-unsaturated carboxylic acid preferably contains (meth)acrylic acid and its ester, and more preferably contains methacrylic acid.
[0015] The chloroprene-based copolymer according to one embodiment of the present invention may include a graft copolymer including a monomer unit derived from chloroprene, a monomer unit derived from a vinyl monomer containing a carboxyl group, and a structure derived from polyvinyl alcohol. The chloroprene-based copolymer according to one embodiment of the present invention is formed by graft copolymerizing polyvinyl alcohol with a polymer containing monomer units derived from chloroprene and monomer units derived from a vinyl monomer containing a carboxyl group, and due to the presence of a polyvinyl alcohol structure around the chloroprene monomer units, it is believed that the copolymer is more stably dispersed in water and has improved storage stability and mechanical stability. The graft copolymer according to one embodiment of the present invention is presumed to contain branch chains containing monomer units derived from chloroprene and monomer units derived from a vinyl monomer containing a carboxyl group, and a backbone chain containing a structure derived from polyvinyl alcohol.
[0016] As described above, the chloroprene copolymer according to the present invention means a polymer containing a monomer unit derived from chloroprene, and includes a polymer containing a monomer unit derived from chloroprene and a monomer unit derived from a vinyl monomer containing a carboxyl group. The chloroprene copolymer according to the present invention also includes both a graft copolymer graft-copolymerized with polyvinyl alcohol and a polymer not graft-copolymerized with polyvinyl alcohol (a polymer not having a polyvinyl alcohol structure).
[0017] The chloroprene copolymer according to one embodiment of the present invention may also contain a structure derived from other compounds (e.g., monomers) other than chloroprene, vinyl monomers containing a carboxyl group, and polyvinyl alcohol. Examples of other monomers include 2,3-dichloro-1,3-butadiene, 1-chloro-1,3-butadiene, butadiene, isoprene, styrene, ethylene, unsaturated nitriles (acrylonitrile, methacrylonitrile, etc.), sulfur, etc. These may be used alone or in combination of two or more. For example, commercially available chloroprene may contain a small amount of 1-chloro-1,3-butadiene as an impurity. 2-chloro-1,3-butadiene containing such a small amount of 1-chloro-1,3-butadiene can also be used as the chloroprene according to the present invention.
[0018] The chloroprene copolymer according to one embodiment of the present invention may contain 30% by mass or less of monomer units and structures derived from other compounds other than the chloroprene, the vinyl monomer containing a carboxyl group, and polyvinyl alcohol, relative to the total of 100% by mass of monomer units derived from the chloroprene and the vinyl monomer containing a carboxyl group in the chloroprene copolymer. The content of the structure derived from the other compound may be, for example, 0, 5, 10, 15, 20, 25, or 30% by mass, and may be within a range between any two of the numerical values exemplified here. By being within the above numerical range, the obtained chloroprene copolymer can exhibit the effect of copolymerizing other monomers without impairing the properties derived from chloroprene, etc.
[0019] The chloroprene-based copolymer according to one embodiment of the present invention may be composed of a non-graft polymer composed of a chloroprene monomer unit and a vinyl monomer unit containing a carboxyl group, and a graft copolymer composed of a chloroprene monomer unit, a vinyl monomer unit containing a carboxyl group, and a structure derived from polyvinyl alcohol.
[0020] The chloroprene copolymer according to one embodiment of the present invention preferably contains 95 to 99.97 parts by mass of monomer units derived from chloroprene, based on 100 parts by mass of the chloroprene copolymer. The content of the monomer units derived from chloroprene is, for example, 95, 96, 97, 98, 99, 99.9, or 99.97 parts by mass, and may be within a range between any two of the numerical values exemplified here.
[0021] The chloroprene copolymer according to the present invention contains 0.70 to 5.00 parts by mass of monomer units derived from a vinyl monomer having a carboxyl group, based on 100 parts by mass of monomer units derived from chloroprene contained in the chloroprene latex composition. The content of the monomer units derived from a vinyl monomer having a carboxyl group is, for example, 0.70, 0.80, 0.90, 1.00, 1.10, 1.20, 1.30, 1.40, 1.50, 1.60, 1.70, 1.80, 1.90, 2.00, 2.10, 2.20, 2.30, 2.40, 2.50, 2.60, 2.70, 2.80, 3.00, 3.50, 3.0 ... , 2.90, 3.00, 3.10, 3.20, 3.30, 3.40, 3.50, 3.60, 3.70, 3.80, 3.90, 4.00, 4.10, 4.20, 4.30, 4.40, 4.50, 4.60, 4.70, 4.80, 4.90, 5.00 parts by mass, and may be within a range between any two of the numerical values exemplified here. By setting the content of the monomer unit derived from the vinyl monomer containing a carboxyl group within the above numerical range and the content of the vinyl monomer containing a free carboxyl group within a specific numerical range, odor, storage stability, and mechanical stability can be improved. In particular, by setting the content of the monomer unit derived from the vinyl monomer containing a carboxyl group to the above lower limit or more, adhesive properties such as heat-resistant adhesive strength can be improved when the obtained chloroprene-based latex composition is used as an aqueous adhesive. In addition, by setting the content of the monomer unit derived from the vinyl monomer containing a carboxyl group to the above upper limit or less, adhesive properties such as water resistance strength can be improved when the obtained chloroprene-based latex composition is used as an aqueous adhesive.
[0022] The chloroprene latex composition according to the present invention contains a part of the added vinyl monomer having a carboxyl group in a state not contained in the chloroprene copolymer, i.e., in a free state. The free vinyl monomer having a carboxyl group will be described later.
[0023] The chloroprene copolymer according to one embodiment of the present invention preferably contains 0.30 to 5.00 parts by mass of a structure derived from polyvinyl alcohol (i.e., a polyvinyl alcohol structure in the graft copolymer) per 100 parts by mass of the chloroprene copolymer. The content of the structure derived from polyvinyl alcohol is, for example, 0.30, 0.50, 1.00, 1.50, 2.00, 2.50, 3.00, 3.50, 4.00, 4.50, or 5.00 parts by mass, and may be within a range between any two of the numerical values exemplified here.
[0024] The chloroprene latex composition according to one embodiment of the present invention may contain a part of the added polyvinyl alcohol in a state that is not graft-copolymerized with the chloroprene copolymer, i.e., in a free state. The free polyvinyl alcohol will be described later.
[0025] The chloroprene-based copolymer according to one embodiment of the present invention contains the above-mentioned amounts of monomer units derived from chloroprene and a vinyl monomer containing a carboxyl group, and a structure derived from polyvinyl alcohol, and further contains a part of the vinyl monomer containing a carboxyl group and a part of the polyvinyl alcohol in a free state, thereby providing a chloroprene-based latex composition which is superior in storage stability and mechanical stability and which is excellent in adhesive properties such as initial peel strength, normal peel strength, water resistant strength, and heat resistant adhesion, and which is capable of providing an aqueous adhesive having a suitable softening point. The amount of each constitutional unit in the chloroprene-based copolymer according to one embodiment of the present invention can be controlled by appropriately adjusting the types and amounts of raw material monomers and various agents in the polymerization recipe for the chloroprene-based copolymer, as well as by adjusting the polymerization conditions (polymerization temperature, time, polymerization rate, amounts and timing of divided addition of raw material monomers and various agents, and temperature of the raw material monomers to be added).
[0026] 1.2 Vinyl monomers containing carboxyl groups The chloroprene latex composition according to one embodiment of the present invention contains a part of the added vinyl monomer containing a carboxyl group in a state not contained in the chloroprene copolymer, i.e., in a free state (monomer state). The vinyl monomer containing a free carboxyl group may be polymerized with another vinyl monomer containing a free carboxyl group to form a polymer. In this specification, the vinyl monomer containing a free carboxyl group also includes a polymer polymerized with another vinyl monomer containing a free carboxyl group.
[0027] The chloroprene-based latex composition according to one embodiment of the present invention may contain 0.10 to 1.40 parts by mass of a vinyl monomer having a free carboxyl group, based on 100 parts by mass of a monomer unit derived from chloroprene contained in the chloroprene-based latex composition. The content of the vinyl monomer having a carboxyl group is, for example, 0.10, 0.20, 0.30, 0.40, 0.50, 0.60, 0.70, 0.80, 0.90, 1.00, 1.10, 1.20, 1.30, or 1.40 parts by mass, and may be within a range between any two of the numerical values exemplified here. By setting the content of the vinyl monomer containing a free carboxyl group within the above numerical range and the content of the monomer unit derived from the vinyl monomer containing a carboxyl group within a specific numerical range, odor, storage stability, and mechanical stability can be improved. In particular, by setting the content of the vinyl monomer containing a free carboxyl group to the above lower limit or more, the adhesive properties can be improved when the obtained chloroprene-based latex composition is used as an aqueous adhesive. In addition, by setting the content of the vinyl monomer containing a free carboxyl group to the above upper limit or less, the odor of the chloroprene-based latex composition can be suppressed, and the adhesive properties such as water resistance can be improved when the obtained chloroprene-based latex composition is used as an aqueous adhesive.
[0028] In the chloroprene latex composition according to one embodiment of the present invention, the copolymerization rate of the vinyl monomer having a carboxyl group, i.e., "the amount of the vinyl monomer unit having a carboxyl group contained in the chloroprene copolymer / (the amount of the vinyl monomer unit having a carboxyl group contained in the chloroprene copolymer+the amount of the vinyl monomer having a free carboxyl group)" is preferably 30% by mass or more. "The amount of the vinyl monomer unit having a carboxyl group contained in the chloroprene copolymer / (the amount of the vinyl monomer unit having a carboxyl group contained in the chloroprene copolymer+the amount of the vinyl monomer having a free carboxyl group)" may be, for example, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, or 80% by mass, and may be within a range between any two of the numerical values exemplified here. The copolymerization rate of the vinyl monomer containing a carboxyl group can be controlled by adjusting polymerization conditions such as polymerization temperature, time, polymerization rate, the amount and timing of the divided addition of raw material monomers and various chemicals, and the temperature of the raw material monomers to be added (for example, by cooling the raw material monomers to be added in divided portions to below freezing point).
[0029] 1.3 Polyvinyl alcohol The chloroprene-based latex composition according to one embodiment of the present invention may contain a part of the added polyvinyl alcohol in a state not contained in the chloroprene-based copolymer (graft copolymer), i.e., in a free state. In this specification, polyvinyl alcohol is also referred to as PVA.
[0030] <Polymerization degree of polyvinyl alcohol> The polyvinyl alcohol according to one embodiment of the present invention preferably has a degree of polymerization of 250 to 1000. The degree of polymerization of polyvinyl alcohol is, for example, 250, 300, 350, 400, 450, 500, 550, 600, 650, 700, 750, 800, 850, 900, 950, or 1000, and may be within a range between any two of the numerical values exemplified here.
[0031] <Saponification degree of polyvinyl alcohol> The polyvinyl alcohol according to one embodiment of the present invention preferably has a degree of saponification of 76 to 95 mol %. The degree of saponification is, for example, 76, 78, 80, 82, 84, 86, 88, 90, 91, 92, 93, 94, or 95 mol %, and may be within a range between any two of the values exemplified here. By setting the degree of polymerization and the degree of saponification of polyvinyl alcohol within the above-mentioned numerical ranges, it becomes easy to adjust the viscosity and dispersibility of the polymerization solution in the polymerization step of the chloroprene-based copolymer to appropriate ranges, and stable polymerization can be performed.
[0032] The chloroprene-based latex composition according to one embodiment of the present invention may contain one or more types of polyvinyl alcohol.
[0033] In one embodiment of the present invention, when the chloroprene-based latex composition is taken as 100 parts by mass, the total amount of polyvinyl alcohol (free polyvinyl alcohol) contained in the chloroprene-based latex composition and the amount of structure derived from polyvinyl alcohol contained in the graft copolymer is preferably 0.30 to 5.00 parts by mass. The total amount of (free) polyvinyl alcohol contained in the chloroprene-based latex composition and the amount of structure derived from polyvinyl alcohol contained in the graft copolymer may be 0.30, 0.50, 1.00, 1.50, 2.00, 2.50, 3.00, 3.50, 4.00, 4.50, or 5.00 parts by mass, and may be within a range between any two of the numerical values exemplified here.
[0034] The chloroprene latex composition according to one embodiment of the present invention preferably contains 0.30 to 5.00 parts by mass of polyvinyl alcohol in a free state that is not graft copolymerized, based on 100 parts by mass of the chloroprene copolymer. The content of the free polyvinyl alcohol is, for example, 0.30, 0.50, 1.00, 1.50, 2.00, 2.50, 3.00, 3.50, 4.00, 4.50, or 5.00 parts by mass, and may be within a range between any two of the numerical values exemplified here.
[0035] In the chloroprene latex composition according to one embodiment of the present invention, the ratio of polyvinyl alcohol incorporated in the chloroprene copolymer, i.e., "the amount of polyvinyl alcohol structure contained in the chloroprene copolymer / (the amount of polyvinyl alcohol structure contained in the chloroprene copolymer+the amount of free polyvinyl alcohol)" is preferably 20% by mass or more. "The amount of polyvinyl alcohol structure contained in the chloroprene copolymer / (the amount of polyvinyl alcohol structure contained in the chloroprene copolymer+the amount of free polyvinyl alcohol)" may be, for example, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, or 80% by mass, and may be within a range between any two of the numerical values exemplified here. The proportion of polyvinyl alcohol incorporated into the chloroprene-based copolymer can be controlled by adjusting polymerization conditions such as polymerization temperature, time, polymerization rate, amounts and timing of divided addition of raw material monomers and various agents, and temperature of the raw material monomers to be added.
[0036] 1.4 Surfactants The chloroprene-based latex composition according to one embodiment of the present invention may contain a surfactant. The surfactant is not particularly limited, and known anionic, nonionic, and cationic surfactants can be used, but it is preferable to include a nonionic surfactant. The nonionic surfactant preferably includes at least one of fatty acid alkanolamides and fatty acid esters. Specifically, sorbitan fatty acid esters such as sorbitan monostearate, sorbitan monolaurate, and sorbitan monopalmitate, fatty acid esters of glycerol such as glycerol monostearate, fatty acid alkanolamides such as lauric acid diethanolamide, myristic acid diethanolamide, and palmitic acid diethanolamide can be mentioned. These may be used alone or in combination of two or more.
[0037] The chloroprene latex composition according to one embodiment of the present invention may contain a surfactant having an HLB value of 3 to 10. The HLB value of the surfactant may be, for example, 3, 4, 5, 6, 7, 8, 9, or 10, and may be within a range between any two of the values exemplified here. In the present invention, the HLB (Hydrophile-Lipophile Balance) value means the HLB value according to Davies' theory, and is expressed as HLB value=Σ(number of hydrophilic groups)-Σ(number of lipophilic groups)+7.
[0038] The chloroprene latex composition according to one embodiment of the present invention may contain 0 to 0.36 parts by mass of a surfactant relative to 100 parts by mass of the chloroprene latex composition. The content of the surfactant is, for example, 0, 0.04, 0.06, 0.08, 0.10, 0.15, 0.20, 0.25, 0.30, 0.32, 0.34, or 0.36 parts by mass, and may be within a range between any two of the numerical values exemplified here.
[0039] The amount of each component contained in the above chloroprene-based latex composition can be controlled by adjusting the production conditions during production of the chloroprene-based latex composition, specifically, the amount of each raw material charged, polymerization conditions, etc. Also, each content can be calculated from the analytical value and the charged amount by the method described in the Examples.
[0040] 1.5 Physical properties of chloroprene-based latex compositions <Storage stability> When 235 g of the chloroprene latex composition according to one embodiment of the present invention is placed in a glass container having a body diameter of 19.5 cm and a volume of 225 ml and stored at 40° C., the period during which the composition settles to a thickness of 2 mm or more on the bottom of the container or the coagulated material remaining on a wire net and dried at 125° C. for 1 hour accounts for 0.005% or more of the solid content of the chloroprene latex composition is preferably 6 weeks or more, more preferably 8 weeks or more. Specifically, the storage stability can be evaluated by the method described in the Examples.
[0041] <Mechanical stability> The chloroprene-based latex composition according to one embodiment of the present invention preferably has a mechanical stability of 0.10% or less. The mechanical stability may be, for example, 0.005, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, or 0.10%, or may be within a range between any two of the values exemplified here. The mechanical stability can be evaluated by the method described in the Examples.
[0042] The storage stability and mechanical stability of the chloroprene-based latex composition according to the present invention can be controlled by appropriately controlling the polymerization step so that the chloroprene-based copolymer contains a specific amount of monomer units derived from a vinyl monomer having a carboxyl group and the chloroprene-based latex composition contains a specific amount of a vinyl monomer having a free carboxyl group.
[0043] The chloroprene-based latex composition according to one embodiment of the present invention preferably has little odor, particularly little irritating odor. Specifically, when 100 mL of the chloroprene-based latex composition is placed in a 250 mL plastic bottle, the bottle is sealed with a lid, and the bottle is stored at 40° C. for 24 hours, the lid is opened, and an olfactory measurement of the headspace gas is performed by an olfactory panelist. It is preferable that the composition has no irritating odor, or has a slight irritating odor, and not a strong irritating odor. The irritating odor can be adjusted by controlling the amount of vinyl monomers containing a free carboxyl group.
[0044] 2. Method for producing chloroprene-based latex composition The method for producing the chloroprene-based latex composition according to the present invention is not particularly limited, and for example, the composition can be produced by the following method. The method for producing the chloroprene-based latex composition according to the present invention can include a polymerization step of polymerizing raw material monomers including a chloroprene monomer and a vinyl monomer having a carboxyl group. In the polymerization step, polyvinyl alcohol and a surfactant are added, and in the polymerization step, at least a part of the raw material monomers can be added in portions after the start of polymerization while being cooled to below freezing point.
[0045] 2.1 Polymerization process In the polymerization step according to the present invention, raw material monomers including a chloroprene monomer are polymerized until a specific polymerization rate (polymerization end conversion rate) is reached. The raw material monomers according to the present invention may include a chloroprene monomer and a vinyl monomer having a carboxyl group. The raw material monomers according to the present invention may further include other monomers other than chloroprene and a vinyl monomer having a carboxyl group. Examples of the other monomers include the monomers listed above.
[0046] <Raw material monomer> (Initial addition) The polymerization step according to one embodiment of the present invention may include an initial addition step of charging at least a part of the raw material monomer used in the polymerization step into a polymerization vessel before the start of polymerization, and may particularly include an initial addition step of charging at least a part of chloroprene into a polymerization vessel. When the raw material monomer used in the polymerization is taken as 100 mass%, the initial addition rate of the raw material monomer at the start of polymerization can be 10.0 to 70.0 mass%. In addition, when the chloroprene monomer used as a raw material is taken as 100 mass%, the initial addition rate of the chloroprene monomer at the start of polymerization is preferably 10.0 to 70.0 mass%. The initial addition rate of the raw material monomer, particularly the chloroprene monomer, at the start of polymerization may be, for example, 10.0, 15.0, 20.0, 25.0, 30.0, 35.0, 40.0, 45.0, 50.0, 55.0, 65.0, or 70.0 mass%, or may be within a range between any two of the numerical values exemplified here.
[0047] In the polymerization step according to one embodiment of the present invention, a part of the monomers other than chloroprene used in the polymerization step can be charged into the polymerization vessel before the start of polymerization, and a part of the monomers other than chloroprene used in the polymerization step can be added after the start of polymerization. As an example, in one embodiment of the present invention, all of the monomers other than chloroprene used in the polymerization step can be charged into the polymerization vessel before the start of polymerization, and all of the vinyl monomers having a carboxyl group used in the polymerization step can be charged into the polymerization vessel before the start of polymerization.
[0048] The amount of the vinyl monomer containing a carboxyl group added is preferably adjusted so that the resulting chloroprene copolymer has the above-mentioned composition, and the amount of the vinyl monomer containing a free carboxyl group in the resulting chloroprene latex composition is within the above-mentioned range. Specifically, it is preferable to add 1.0 to 5.0 parts by mass to 100 parts by mass of the raw material monomer used in the polymerization step. The amount of the vinyl monomer containing a carboxyl group added is, for example, 1.0, 2.0, 3.0, 4.0, or 5.0 parts by mass, and may be within a range between any two of the numerical values exemplified here.
[0049] (split addition) The polymerization step according to the present invention may include a raw material monomer divisional addition step. In the raw material monomer divisional addition step, the remaining raw material monomer, particularly chloroprene, may be added in divisions after the start of polymerization. In the raw material monomer divisional addition step, a monomer other than chloroprene may be added in divisions after the start of polymerization. Divisional addition means adding the remaining raw material monomer, particularly chloroprene, in at least two or more portions. The number of divisional additions may be at least two or more portions, preferably at least five or more portions, and more preferably ten or more portions. The divisional addition includes continuous addition in which the remaining raw material monomer, particularly chloroprene, is continuously added at a constant flow rate, and the divisional addition is preferably continuous addition.
[0050] In one embodiment of the present invention, the divided addition can be started 30 to 150 minutes after the start of polymerization (the point when the polymerization rate relative to the total monomers used in the polymerization is 0%). The divided addition can be started, for example, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, 100, 105, 110, 115, 120, 125, 130, 135, 140, 145, or 150 minutes after the start of polymerization, and may be within a range between any two of the numerical values exemplified here.
[0051] In one embodiment of the present invention, the divided addition can be carried out over, for example, 30 to 1200 minutes. The divided addition time (time required for divided addition) is, for example, 30, 60, 100, 200, 300, 400, 500, 600, 700, 800, 900, 1000, 1100, or 1200 minutes, and may be within a range between any two of the numerical values exemplified here.
[0052] In one embodiment of the present invention, the polymerization time from the start of polymerization to the end of polymerization conversion can be 60 to 1800 minutes, for example, 60, 100, 200, 300, 400, 500, 600, 700, 800, 900, 1000, 1100, 1200, 1300, 1400, 1500, 1600, 1700, or 1800 minutes, and may be within a range between any two of the numerical values exemplified here.
[0053] In one embodiment of the present invention, the divided addition can be carried out over a period of 20 or more years, assuming that the polymerization time from the start of polymerization to the end of polymerization conversion is 100. Here, the divided addition can be considered to start with the first divided addition added after the start of polymerization and end with the last divided addition when all monomers are added. The divided addition can be 20 to 70, for example, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, assuming that the polymerization time is 100, and may be within a range between any two of the numerical values exemplified here.
[0054] In the production method of the present invention, at least a part of the raw material monomer can be added in portions after the start of polymerization while being cooled to below freezing point. By cooling at least a part of the raw material monomer to below freezing point and adding in portions, the progress of polymerization can be more appropriately controlled. In one embodiment of the present invention, it is preferable to cool the chloroprene monomer to below freezing point and add in portions. At least a part of the raw material monomer can be cooled to, for example, 0, -5, -10, -15, -20, -25, or -30°C, and may be within a range between any two of the numerical values exemplified here.
[0055] It is presumed that by initially adding a specific portion of the chloroprene monomer used in polymerization and then adding the remainder in portions at a specific timing over a specific period of time, particularly as a temperature-controlled raw material monomer, it becomes easier to control the copolymerization rate of the carboxyl group-containing vinyl monomer and the proportion of polyvinyl alcohol incorporated in the chloroprene-based copolymer to a higher degree, and thus a chloroprene-based latex composition having less odor and excellent storage stability and mechanical stability can be obtained.
[0056] <Emulsifier> In the polymerization step according to the present invention, polyvinyl alcohol and a surfactant can be added. Polyvinyl alcohol and the surfactant function as an emulsifier. The polyvinyl alcohol and the surfactant are preferably the polyvinyl alcohol and the surfactant in the above-described embodiments.
[0057] The addition amount of polyvinyl alcohol is preferably adjusted so that the resulting chloroprene copolymer has the above-described composition and the amount of free polyvinyl alcohol in the resulting chloroprene latex composition is within the above-described range. Specifically, it is preferably added in an amount of 1.0 to 5.0 parts by mass with respect to 100 parts by mass of the raw material monomer used in the polymerization step. The addition amount of polyvinyl alcohol is, for example, 1.0, 2.0, 3.0, 4.0, 5.0 parts by mass, and may be within the range between any two of the numerical values exemplified herein.
[0058] In the polymerization step according to one embodiment of the present invention, a surfactant may be further added. The addition amount of the surfactant can be added in an amount of 0 to 0.60 parts by mass with respect to 100 parts by mass of the raw material monomer used in the polymerization step. The addition amount of the surfactant is, for example, 0, 0.15, 0.20, 0.25, 0.30, 0.35, 0.40, 0.45, 0.50, 0.55, 0.60 parts by mass, and may be within the range between any two of the numerical values exemplified herein.
[0059] In the polymerization step according to one embodiment of the present invention, all of the emulsifier used in the polymerization step can be charged into the polymerization vessel before the start of polymerization. Further, in the polymerization step according to one embodiment of the present invention, at least a part of the emulsifier used in the polymerization step can be added separately after the start of polymerization.
[0060] <pH adjuster> In the polymerization step according to one embodiment of the present invention, a pH adjuster can be added. Examples of the pH adjuster include potassium hydroxide, sodium hydroxide, diethanolamine, diisopropanolamine, and triisopropanolamine. Two or more types of pH adjusters may be used in combination.
[0061] <Reducing agent> In the polymerization step according to one embodiment of the present invention, a reducing agent can be added. Examples of the reducing agent include potassium pyrosulfite, potassium sulfite, potassium hydrogen sulfite, potassium phosphate, potassium hydrogen phosphate, sodium hydrogen sulfite, and sodium sulfite. The amount of the reducing agent added can be 0.01 to 3.0 parts by mass relative to 100 parts by mass of the raw material monomer used in the polymerization step.
[0062] In the polymerization step according to one embodiment of the present invention, a polymerization initiator can be used. As the polymerization initiator, inorganic peroxides such as potassium persulfate, ammonium persulfate, sodium persulfate, and hydrogen peroxide; organic peroxides such as benzoyl peroxide, etc. can be used. These polymerization initiators can be used alone or in combination of two or more. The amount of the polymerization initiator used is preferably 0.01 to 10 parts by mass relative to 100 parts by mass of the raw material monomer used in the polymerization step.
[0063] <Chain transfer agent> In the polymerization step according to one embodiment of the present invention, a chain transfer agent can be used. The chain transfer agent is not particularly limited, and for example, known chain transfer agents such as long-chain alkyl mercaptans such as n-dodecyl mercaptan, tert-dodecyl mercaptan, and n-octyl mercaptan, dialkyl xanthogen disulfides such as diisopropyl xanthogen disulfide and diethyl xanthogen disulfide, and iodoform can be used. These may be used alone or in combination of two or more. The amount of the chain transfer agent added can be 0.001 to 10 parts by mass based on 100 parts by mass of the raw material monomer used in the polymerization step.
[0064] In the polymerization step according to one embodiment of the present invention, all of the chain transfer agent used in the polymerization step can be charged into the polymerization vessel before the polymerization starts. Also, in the polymerization step according to one embodiment of the present invention, a part of the chain transfer agent used in the polymerization step can be charged into the polymerization vessel before the polymerization starts, and at least a part of the chain transfer agent can be added after the polymerization starts. As an example, the divided addition of the chain transfer agent can be started simultaneously with the divided addition of the monomer. When at least a part of the chain transfer agent is added before the initiation of polymerization and the remaining part of the chain transfer agent is added after the initiation of polymerization, the remaining chain transfer agent can be added in one or more portions, or can be added continuously at a constant flow rate. For example, the chain transfer agent can be added in portions continuously over a period of time similar to that of the portionwise addition of the chloroprene monomer. When at least a part of the chain transfer agent is added after the initiation of polymerization, 20 to 95 parts by mass of 100 parts by mass of the chain transfer agent used in the polymerization step can be added after the initiation of polymerization. In this case, the amount of the chain transfer agent added after the initiation of polymerization can be, for example, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, or 95 parts by mass, and may be within a range between any two of the numerical values exemplified here.
[0065] <Polymerization temperature> The polymerization temperature is preferably in the range of 0 to 55° C. from the viewpoint of ease of reaction control, etc. From the viewpoint of carrying out the polymerization reaction more smoothly and safely, it is preferable that the lower limit of the polymerization temperature is 10° C. or more and the upper limit is 55° C. or less.
[0066] <Polymerization completion conversion rate> In the polymerization step according to the present invention, after the desired polymerization conversion rate is reached, the polymerization reaction can be terminated by adding a polymerization terminator, and the conversion rate at the end of the polymerization is defined as the polymerization termination conversion rate. The polymerization termination conversion rate can be in the range of 50 to 99.9% by mass. The polymerization termination conversion rate is, for example, 50, 60, 70, 80, 85, 90, 91, 92, 93, 94, 95, 96, 97, 98, 99, 99.5, or 99.9% by mass, and may be within a range between any two of the numerical values exemplified here.
[0067] <Polymerization terminator> Examples of the polymerization terminator include diethylhydroxyamine, thiodiphenylamine, 4-tert-butylcatechol, 2,2'-methylenebis(4-ethyl-6-tert-butylphenol), etc. The amount of the polymerization terminator added may be 0.02 to 0.1 parts by mass relative to 100 parts by mass of the total monomers used in the polymerization step.
[0068] 2.2 Removal of unreacted monomer The production method according to one embodiment of the present invention may include a step of removing an unreacted monomer, in which the unreacted monomer after the completion of polymerization is removed from the polymerization solution after the completion of polymerization by a conventional method such as steam stripping or reduced pressure heating evaporation, to obtain a chloroprene-based latex composition.
[0069] The solids concentration of the chloroprene-based latex composition in the polymerization solution at the end of the polymerization can be, for example, 20, 25, 30, 35, 40, 45, 50, 55, or 60% by mass, and may be within a range between any two of the numerical values exemplified here.
[0070] 3. Adhesive (water-based adhesive) The chloroprene-based latex composition according to the present invention can be used for an adhesive, particularly for an aqueous adhesive. An adhesive according to one embodiment of the present invention includes the above-mentioned chloroprene-based latex composition. The adhesive can be an aqueous adhesive. An adhesive according to one embodiment of the present invention can include the above-mentioned chloroprene-based latex composition, a tackifier resin, and a metal oxide.
[0071] <Tackifier resin> Examples of tackifier resins include rosin resins, polymerized rosin resins, α-pinene resins, β-pinene resins, terpene phenol resins, C5 fraction petroleum resins, C9 fraction petroleum resins, C5 / C9 fraction petroleum resins, DCPD petroleum resins, alkylphenol resins, xylene resins, coumarone resins, coumarone indene resins, etc. These may be used alone or in combination of two or more.
[0072] The method of adding the tackifier resin is not particularly limited, but it is preferable to add it after making it into an aqueous emulsion in order to disperse the resin uniformly in the adhesive. To make the tackifier resin into an aqueous emulsion, there is a method in which the tackifier resin is dissolved in an organic solvent such as toluene, emulsified / dispersed in water using an emulsifier, and then the organic solvent is removed by heating under reduced pressure, or a method in which the resin is pulverized into fine particles and emulsified / dispersed.
[0073] The amount of tackifier resin added (in terms of solid content) can be 10 to 50 parts by mass relative to 100 parts by mass of the adhesive. The amount of tackifier resin added (in terms of solid content) can be, for example, 10, 15, 20, 25, 30, 35, 40, 45, or 50 parts by mass, and may be within a range between any two of the numerical values exemplified here.
[0074] <Metal oxide> Examples of metal oxides include zinc oxide, titanium oxide, iron oxide, etc. These may be used alone or in combination of two or more.
[0075] The amount of metal oxide added (in terms of solid content) can be 0.1 to 5.0 parts by mass relative to 100 parts by mass of the adhesive, and may be, for example, 0.1, 0.2, 0.5, 1.0, 2.0, 3.0, 4.0, or 5.0 parts by mass, or may be within a range between any two of the numerical values exemplified here.
[0076] In addition to the above-mentioned components, the adhesive according to one embodiment of the present invention may contain, as appropriate, a pH adjuster, a plasticizer, a filler, an antioxidant, a pigment, a colorant, a wetting agent, an antifoaming agent, a thickener, other resin emulsions (latex), and the like.
[0077] Adhesives prepared using the chloroprene-based latex composition of the present invention can be used for bonding the same types of adherends, such as paper, wood, cloth, leather, rubber, plastic, plastic foam, pottery, glass, ceramics, and metals, or for bonding different types of adherends.
[0078] The chloroprene-based latex composition according to one embodiment of the present invention can be prepared, for example, by the following method.
[0079] <Adhesive manufacturing> 50 parts by mass of a tackifier resin (Tamanol E-100 manufactured by Arakawa Chemical Industries Co., Ltd.) and 1 part by mass of a metal oxide (zinc oxide: AZ-SW manufactured by Osaki Kogyo Co., Ltd.) are added to 100 parts by mass (solid content basis) of a chloroprene-based latex composition, and the mixture is stirred using a Three-One motor. A thickener (RM-8W manufactured by Rohm and Haas Co., Ltd.) is added so that the viscosity of the solution becomes 3000 to 4000 mPa s at 25°C x 30 rpm, to obtain an adhesive.
[0080] The adhesive according to the invention preferably has the following properties for adhesive samples prepared as follows: <Preparation of adhesive samples> The obtained adhesive was applied to two pieces of canvas (25 x 150 mm) at 300 g (solid content) / m 2 The adhesive is applied with a brush so that the adhesive becomes as shown below, dried for 9 minutes in an 80°C atmosphere, and left at room temperature for 1 minute, after which the coated surfaces are laminated together and pressed with a hand roller to obtain an adhesive sample. The obtained adhesive sample is evaluated as follows.
[0081] <Initial peel strength> The aqueous adhesive according to one embodiment of the present invention preferably has an initial peel strength of 3.0 N / mm or more in a T-peel test measured at a tensile speed of 200 mm / min using a tensile tester when the adhesive sample is left at room temperature for 10 minutes after roller compression. The initial peel strength may be, for example, 3.0, 3.5, 4.0, 4.5, 5.0, 5.5, or 6.0 N / mm, or may be within a range between any two of the values exemplified here.
[0082] <Normal peel strength> The aqueous adhesive according to one embodiment of the present invention preferably has a normal peel strength of 4.0 N / mm or more in a T-peel test (normal peel strength) measured using a tensile tester at a tensile speed of 200 mm / min after leaving the adhesive sample at room temperature for 5 days. The normal peel strength is, for example, 4.0, 4.5, 5.0, 5.1, 5.2, 5.3, 5.4, 5.5, 5.6, 5.7, 5.8, 5.9, or 6.0 N / mm, and may be within a range between any two of the values exemplified here.
[0083] <Water resistance> The aqueous adhesive according to one embodiment of the present invention preferably has a water resistance of 2.2 N / mm or more in a T-peel test (water resistance) measured at a tensile speed of 200 mm / min using a tensile tester after leaving the adhesive sample at room temperature for 5 days and then immersing it in water at 23° C. for 2 days. The water resistance is, for example, 2.2, 2.4, 2.6, 2.8, 3.0, 3.2, 3.4, 3.6, 3.8, or 4.0 N / mm, and may be within a range between any two of the values exemplified here.
[0084] <Heat-resistant adhesive strength> The aqueous adhesive according to one embodiment of the present invention preferably has a heat-resistant adhesive strength of 1.2 N / mm or more in a T-peel test in which the adhesive sample is left at room temperature for 5 days, and then left in an atmosphere at 80° C. for 15 minutes and then measured at a speed of 200 mm / min in an atmosphere at 80° C. The heat-resistant adhesive strength is, for example, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, or 2.0 N / mm, and may be within a range between any two of the numerical values exemplified here.
[0085] <Softening point> The aqueous adhesive according to one embodiment of the present invention can have a softening point of 40 to 80° C. when the obtained adhesive is applied to two pieces of canvas (25×150 mm) with a brush to a thickness of 0.5 mm, bonded together, and heated at 2° C. / 5 minutes while applying a load of 500 g using a T-peeler, and the temperature at which the adhesive is peeled off is taken as the softening point. The softening point is, for example, 40, 45, 50, 55, 60, 65, 70, 75, or 80° C., and may be within a range between any two of the numerical values exemplified here.
[0086] The chloroprene-based latex composition according to one embodiment of the present invention preferably has the above-mentioned properties when made into an adhesive having the above-mentioned formulation, specifically, the formulation described in the Examples.
[0087] Adherends that can be bonded with the adhesive of one embodiment of the present invention include foams made of materials such as polyurethane, ethylene-vinyl acetate copolymer, and polyethylene, wood, cloth, textiles, paper, leather, rubber, pottery, glass, ceramics, and metals, and the like. The adhesive can bond adherends of the same type or different types. EXAMPLES
[0088] The present invention will be described in more detail below based on examples, but the present invention is not limited to these examples.
[0089] <Production of Chloroprene-Based Latex Composition> Example 1 In a 10-liter reactor, 106.3 parts by mass of water, 3.5 parts by mass of polyvinyl alcohol (polymerization degree 300, saponification degree 88 mol%), and 0.39 parts by mass of a nonionic surfactant were added under a nitrogen gas flow and dissolved. While stirring the resulting mixture, 39.2 parts by mass of chloroprene, 2.0 parts by mass of methacrylic acid, and 0.10 parts by mass of octyl mercaptan were further added and stirred at 30°C for 10 minutes (initial addition (hereinafter also referred to as initial addition)). 0.1 parts by mass of sodium sulfite was added as a reducing agent, and polymerization was started at 35°C under a nitrogen atmosphere using potassium persulfate as an initiator. After 90 minutes had elapsed from the start of polymerization (the point at which the polymerization rate relative to the total monomers used in polymerization was 0%), the divided addition process was started, and 58.8 parts by mass of chloroprene and 0.15 parts by mass of octyl mercaptan were continuously added over 300 minutes (continuous addition (hereinafter also referred to as continuous addition)). For the divided addition, chloroprene cooled to -12°C was used. After that, when the polymerization rate reached 97.97%, an emulsion of phenothiazine was added to terminate the polymerization. After adjusting the pH of the polymerization solution to 7.2 using a 45% aqueous diethanolamine solution, unreacted monomers were removed under reduced pressure to obtain a chloroprene-based latex composition. Further, water was added to adjust the solid content of the chloroprene-based latex composition to 50% by mass. The finally obtained chloroprene-based latex composition contained 0.19 parts by mass of a nonionic surfactant per 100 parts by mass of the chloroprene-based latex composition.
[0090] (Examples 2 to 6, Comparative Examples 1 to 10) A chloroprene-based latex composition having a solid content concentration of 50 mass % was produced in the same manner as in Example 1, except that the polymerization recipe and polymerization conditions were as shown in Tables 1 to 3.
[0091] <Evaluation of Chloroprene-Based Latex Composition> (Amount of each component in the chloroprene-based latex composition) The composition of each component shown below was calculated from the charged amount and analytical values. Amount of polyvinyl alcohol structure (including free polyvinyl alcohol) per 100 parts by mass of chloroprene-based latex composition Amount of polyvinyl alcohol structure in the graft copolymer (in the chloroprene copolymer) per 100 parts by mass of the chloroprene copolymer Amount of free polyvinyl alcohol per 100 parts by mass of chloroprene copolymer The amount of vinyl monomer units containing a carboxyl group in a chloroprene-based copolymer per 100 parts by mass of monomer units derived from chloroprene in the chloroprene-based copolymer The amount of vinyl monomer containing a free carboxyl group per 100 parts by mass of monomer units derived from chloroprene in a chloroprene copolymer The results are shown in Tables 1 to 3.
[0092] (Amount of polyvinyl alcohol structure in graft copolymer) The amount of polyvinyl alcohol structure in the graft copolymer was calculated by the following method. First, the amount of free polyvinyl alcohol not graft-copolymerized was quantified by the following method, and the amount of polyvinyl alcohol structure in the graft copolymer was calculated by subtracting the amount of free polyvinyl alcohol from the amount of polyvinyl alcohol charged.
[0093] Preparation of Reagents 4 g of boric acid was dissolved in 96 mL of pure water to prepare a 4% aqueous solution of boric acid. An aqueous solution of potassium iodide was prepared by dissolving 2.5 g of potassium iodide in approximately 70 mL of pure water. 1.27 g of iodine was weighed out and dissolved in the aqueous solution of potassium iodide prepared in advance, and pure water was added until the total amount became 100 mL to prepare an iodine solution.
[0094] Preparation of PVA standard solution 0.1g of PVA was precisely weighed into a 100mL measuring flask, 50-60mL of pure water was added, and the solution was dissolved in a water bath (approximately 95℃). After cooling to room temperature, pure water was added up to the mark and mixed well. 10mL was then taken and placed in a 100mL measuring flask, pure water was added up to the mark and mixed well to prepare a standard solution with a PVA concentration of 0.1mg / mL.
[0095] -Creating a calibration curve The above standard solution was dispensed into 50 mL measuring flasks at 1, 5, 10, 15, and 20 mL, and 15 mL of 4% boric acid solution was added to each, followed by adding pure water until the total volume reached 45 mL. To each solution, 3 mL of iodine solution was added, and pure water was added up to the mark, mixed well, and solutions with PVA concentrations of 2, 10, 20, 30, and 40 mg / L were prepared. Using a blank solution prepared without adding iodine as a control, the absorbance was measured using a spectrophotometer at a wavelength of 650 nm and a cell glass of 10 mm, and a concentration-absorbance calibration curve was created.
[0096] Preparation of measurement samples 9 g of the chloroprene-based latex composition of each Example and Comparative Example was weighed into a 200 mL beaker, and 171 g of pure water was added while stirring to dilute the composition by 20 times by mass. 100 g of the diluted solution (50 g x 2) was placed in a cell and centrifuged at 6000 rpm x 30 minutes. 1 mL of the supernatant was taken into a 50 mL measuring flask, 15 mL of 4% boric acid aqueous solution was added, and pure water was added until the total volume was 45 mL. Furthermore, 3 mL of iodine solution was added, pure water was added up to the mark, and the mixture was mixed well to prepare a measurement sample.
[0097] -Measurement of absorbance Using the blank solution as a control, the absorbance was measured using a spectrophotometer at a wavelength of 650 nm and a cell glass of 10 mm. The measurement was carried out by diluting the original chloroprene-based latex composition 1000 times (20 times dilution x 50 times dilution).
[0098] Calculation of PVA concentration, amount of free polyvinyl alcohol, amount of polyvinyl alcohol structure in graft copolymer The PVA concentration of the measured sample, S, is calculated using the following formula: c was calculated. S c =ABS×A S c : PVA concentration in measuring flask [mg / L], ABS: absorbance, A: coefficient (calculated from the calibration curve using Lotus 1-2-3) Next, the free polyvinyl alcohol concentration in the chloroprene-based latex composition was calculated using the following formula. L c =S c ×C / B L c : Free polyvinyl alcohol concentration in chloroprene-based latex composition [g / kg], B: Amount of dilution solution [g] C: Volume of supernatant [g]
[0099] Finally, the amount of free polyvinyl alcohol in the chloroprene-based latex composition and the amount of polyvinyl alcohol structure in the graft copolymer were calculated by the following formulas. PVA F =L c ×L Q PVA F : Amount of free polyvinyl alcohol [g] L Q : Amount of chloroprene-based latex composition [kg] PVA G =PVA Q -PVA F PVA G : Amount of polyvinyl alcohol structure in the graft copolymer [g] PVA Q : Amount of polyvinyl alcohol [g]
[0100] The obtained PVA G was divided by the amount of the chloroprene copolymer in the chloroprene latex composition to calculate the amount of polyvinyl alcohol structure in the graft copolymer relative to 100 parts by mass of the chloroprene copolymer. The "amount of chloroprene copolymer" was the total of the amount of chloroprene monomer units, the amount of vinyl monomer units containing a carboxyl group (excluding vinyl monomers containing a free carboxyl group), and the amount of polyvinyl alcohol structure (excluding free polyvinyl alcohol) in the chloroprene latex composition. Further, the amount of PVA structure contained in the chloroprene-based copolymer / (amount of PVA structure contained in the chloroprene-based copolymer+amount of free PVA) was calculated.
[0101] (Amount of copolymerization of carboxyl group-containing vinyl monomer) The chloroprene copolymers according to the examples and comparative examples have a high gel content, and are used to measure the amount of methacrylic acid copolymerized. 1 In H-NMR measurement, it cannot be dissolved in the measurement solvent. Therefore, the methacrylic acid / chloroprene peak area ratio was calculated by PyGC / MS (SIM method) and standard samples with different amounts of methacrylic acid copolymerized (without gel content) were used. 1 H-NMR measurement is possible) 1 The amount of methacrylic acid copolymerized was calculated using the methacrylic acid / chloroprene peak area ratio (MAA copolymerization amount) by H-NMR vs. the methacrylic acid / chloroprene peak area ratio by PyGC / MS (SIM method).
[0102] Preparation of samples for PyGC / MS (SIM method) The samples were freeze-dried and extracted with an ethanol-toluene azeotrope (ETA). The residue after drying was measured by PyGC / MS (SIM method).
[0103] ·PyGC / MS (SIM method) Using methacrylic acid: m / z = 86 and chloroprene: m / z = 91, the methacrylic acid / chloroprene peak area ratio was calculated under the following measurement conditions. Equipment: JEOL Jms-Q1050GC GC column: DB-WAX 60m*0.25mm(0.5μm) Column temperature: 100℃(0min)→10℃ / min→240℃(11min) Inlet temperature: 240℃ Carrier: He 1.0mL / min (Split 1:30) MS interface temperature: 240℃ Ion source temperature: 250℃ Ionization current: 50μA Ionization voltage: 70 eV Detector voltage: -1200V Ionization method: EI SIM (m / z: 86.91) Py Frontier Labs PY-3030D Thermal decomposition temperature: 590℃ Sample size: 0.1 mg Interface temperature: 300℃
[0104] · 1 Preparation of samples for H-NMR measurements The chloroprene-based latex composition was purified using methanol and xylene to obtain a sample. Approximately 30 mg of the sample was dissolved in approximately 1 mL of deuterated chloroform, and the measurement was performed.
[0105] · 1 H-NMR Equipment configuration: Solution NMR (using 5 mm probe) Measurement conditions Analytical equipment: Superconducting nuclear magnetic resonance device ECX-400 manufactured by JEOL Observation kernel: 1 H Measurement conditions: Single Pulse Sample tube rotation speed: 12Hz Measurement temperature: 30℃ Pulse width: 3.5μsec (45° pulse) Repeat time: 7 seconds Number of times: 128
[0106] From the methacrylic acid / chloroprene peak area ratio, the amount of vinyl monomer containing a carboxyl group in the chloroprene copolymer was calculated relative to 100 parts by mass of monomer units derived from chloroprene in the chloroprene copolymer. In addition, the amount of methacrylic acid copolymerized was subtracted from the charged amount to calculate the amount of free vinyl monomer units containing a carboxyl group. In addition, "the amount of vinyl monomer units containing a carboxyl group contained in the chloroprene copolymer / (the amount of vinyl monomer units containing a carboxyl group contained in the chloroprene copolymer+the amount of free vinyl monomers containing a carboxyl group)" was calculated. The "amount of free vinyl monomer units containing a carboxyl group" includes vinyl monomers containing a carboxyl group and polymers composed of vinyl monomers containing a carboxyl group that are not bonded to the chloroprene copolymer.
[0107] (Storage stability) Eight bottles were prepared by sealing 235 g of the chloroprene latex composition in a glass container having a body diameter of 19.5 cm and a volume of 225 ml. All of the bottles were stored at 40° C., and one of the bottles was taken out every week, and the chloroprene latex in the bottle was filtered through a 100-mesh wire screen. The time until the thickness of the chloroprene latex composition remaining at the bottom of the glass container became 2 mm or more, or until the coagulated material remaining on the wire screen was dried at 125° C. for 1 hour and the coagulated material became 0.005% or more of the solid content of the chloroprene latex composition was recorded. The evaluation results are shown in Tables 1 to 3.
[0108] (mechanical stability) Using a Marlon testing apparatus in accordance with JIS K 6828, the amount of coagulated material generated when a shear force of a load of 10 kg and a rotation speed of 1000 rpm was applied for 10 minutes to 50 g of a chloroprene-based latex composition (solid content concentration 50% by mass) was evaluated. The coagulated material attached to the rotor of the Marlon testing apparatus was collected on a SUS80 mesh wire screen, washed with pure water, dried under reduced pressure, and the mass was measured. The evaluation results are shown in Tables 1 to 3. The values in the tables were calculated by the following formula after drying and weighing the generated coagulated material, and the smaller the value, the more stable it is against shear force. Mechanical stability (%)=Dry mass of coagulum [g] / 50[g]×100
[0109] (Odor evaluation) 100 mL of the chloroprene-based latex composition was placed in a 250 mL plastic bottle, which was then sealed with a lid and stored at 40°C for 24 hours. After that, the lid was opened and an olfactory panel measured the headspace gas and determined the intensity of the irritating odor according to the following criteria. ○: No irritating odor △: Has a slightly pungent odor ×: Has a strong irritating odor
[0110] <Preparation of adhesive> The chloroprene-based latex composition of each Example and Comparative Example, a tackifier resin (terpene phenol, manufactured by Arakawa Chemical Industries, Ltd., Tamanor E-100 (solid concentration 53%)), and a metal oxide (aqueous zinc oxide, manufactured by Osaki Industrial Co., Ltd., AZ-SW (solid concentration 50%)) were mixed in the proportions shown in Tables 1 to 3 to prepare adhesives.
[0111] <Adhesive evaluation> The obtained adhesive was applied to two pieces of canvas (25 x 150 mm) at 300 g (solid content) / m 2 The adhesive was applied with a brush so that the adhesive was applied to the adhesive layer, dried for 9 minutes in an 80°C atmosphere, and allowed to stand at room temperature for 1 minute. The applied surfaces were then laminated together and pressed with a hand roller to obtain an adhesive sample. The obtained adhesive sample was evaluated as follows. The evaluation results are shown in Tables 1 to 3.
[0112] (Initial peel strength) The obtained bonded sample was pressed with a roller and then left at room temperature for 10 minutes. A T-peel test was performed using a tensile tester at a tensile speed of 200 mm / min.
[0113] (Normal peel strength) The obtained bonded sample was allowed to stand at room temperature for 5 days, and then subjected to a T-peel test at a tensile speed of 200 mm / min using a tensile tester.
[0114] (Water resistance) The obtained bonded sample was left to stand at room temperature for 5 days, and then further immersed in water at 23° C. for 2 days, and a T-peel test was performed using a tensile tester at a tensile speed of 200 mm / min.
[0115] (Heat-resistant adhesive strength) The obtained adhesion sample was left at room temperature for 5 days, and then further left in an 80° C. atmosphere for 15 minutes, and a T-peel test was performed in an 80° C. atmosphere at a speed of 200 mm / min.
[0116] (softening point) The obtained adhesive was applied to two pieces of canvas (25 x 150 mm) with a brush to a thickness of 0.5 mm, and the pieces were bonded together. Using a T-type peeler, the temperature was raised at 2°C / 5 minutes while a load of 500 g was applied, and the temperature at which the pieces peeled off was recorded as the softening point.
[0117] [Table 1]
[0118] [Table 2]
[0119] [Table 3]
Claims
1. A chloroprene-based latex composition comprising a chloroprene-based copolymer and polyvinyl alcohol, The chloroprene copolymer contains a monomer unit derived from chloroprene and a monomer unit derived from a vinyl monomer containing a carboxyl group, The chloroprene-based copolymer contains 0.70 to 5.00 parts by mass of monomer units derived from the vinyl monomer containing a carboxyl group per 100 parts by mass of monomer units derived from the chloroprene, The chloroprene-based latex composition contains 0.10 to 1.40 parts by mass of a vinyl monomer containing a free carboxyl group per 100 parts by mass of the monomer units derived from the chloroprene. Chloroprene-based latex compositions.
2. The chloroprene copolymer is 2. The chloroprene-based latex composition according to claim 1, comprising a graft copolymer comprising a monomer unit derived from the chloroprene, a monomer unit derived from the vinyl monomer containing a carboxyl group, and a structure derived from polyvinyl alcohol.
3. The chloroprene-based latex composition according to claim 1 or claim 2, wherein the chloroprene-based copolymer contains 0.30 to 5.00 parts by mass of a structure derived from the polyvinyl alcohol when the chloroprene-based copolymer is taken as 100 parts by mass.
4. The chloroprene-based latex composition according to claim 1 or 2, further comprising a nonionic surfactant.
5. 3. The chloroprene-based latex composition according to claim 1, wherein the vinyl monomer containing a carboxyl group contains an α,β-unsaturated carboxylic acid.
6. A method for producing the chloroprene-based latex composition according to claim 1 or 2, comprising the steps of: The production method includes a polymerization step of polymerizing raw material monomers including a chloroprene monomer and a vinyl monomer having a carboxyl group, In the polymerization step, polyvinyl alcohol and a surfactant are added, In the polymerization step, the raw material monomers are added in portions after the initiation of polymerization while being cooled to below freezing point at least in part.
7. 3. A water-based adhesive comprising the chloroprene-based latex composition according to claim 1 or 2.
Citation Information
Patent Citations
Polychloroprene latex composition, adhesive, coating material and production method for the same composition
JP2005008859A
Polychloroprene latex composition
JP3294910B2